Deciphering the Link Between ERUPR Signaling and MicroRNA in Pathogenesis of Alzheimer’s Disease - Yasmeen, Nusrath; Datta, Manali; Kumar, Vikram; Alshehri, Fahad S.; Almalki, Atiah H.; Haque, Shafiul (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative proteinopathic disease. The deposits of misfolded Amyloid β and Tau proteins in the brain of patients with AD suggest an imbalance in endoplasmic reticulum (ER) proteostasis. ER stress is due to accumulation of aberrant proteins in the ER lumen, which then leads to activation of three sensor protein pathways that ultimately evokes the adaptive mechanism of the unfolded protein response (UPR). The UPR mechanism operates via adaptive UPR and the apoptotic UPR. Adaptive UPR tries to restore imbalance in ER hemostasis by decreasing protein production, enhanced chaperone involvement to restore protein folding, misfolded protein decay by proteasome, and suppression of ribosomal translation ultimately relieving the excessive protein load in the ER. Subsequently, apoptotic UPR activated under severe ER stress conditions triggers cell death. MicroRNAs (miRNAs) are small non-coding protein causing dysregulated translational of mRNAs in a sequential manner. They are considered to be critical elements in the maintenance of numerous cellular activities, hemostasis, and developmental processes. Therefore, upregulation or downregulation of miRNA expression is implicated in several pathogenic processes. Evidence from scientific studies suggest a strong correlation between ERUPR signaling and miRNA dysregulation but the research done is still dormant. In this review, we summarized the cross-talk between ER stress, and the UPR signaling processes and their role in AD pathology by scrutinizing and collecting information from original research and review articles.